13C tracer deposition in EAST D and He plasmas investigated by high-throughput deuteron nuclear reaction analysis mapping. (December 2020) - Möller, S.; Ding, R.; Xie, H.; Gao, B.F.; Wang, B.G.; Peng, J.; Liu, S.C.; Gao, W.; Kirschner, A.; Breuer, U.; Wienhold, P.; Krug, R.; et al.
Highlights: 13 CD4 co-deposits from EAST D- and He-plasma tracer injection. 1.4 MeV deuteron ion beam analysis in ≈ 3000 points on about 8500 mm 2 . 24% (D plasma) and 16% (He plasma) deposition efficiency. 98% of 13 C found within 20 mm around the injection hole. D-NRA yields additional physics via D/C ratios, ExB correlation and fall-off length. Abstract: Rare isotope tracer injection represents an established way for following particle transport in fusion research, but a tracer experiment is only as good as the tracer can be followed and separated from the common isotope. Physical models for transport analysis such as ERO2.0 require accurate total amounts of deposition with high spatial resolution. This work describes an extended high throughput NRA post analysis approach together with the surface analysis results of 2 technically rough graphite-tiles of 150x150 mm 2 surface area exposed to D and He plasmas in EAST. The applied 1.43 MeV deuteron beam NRA offers percent range accuracy for layer thicknesses ranging from few 10 nm to 20 µm. Optimisation of the beam line and beam optics enables operation with ≤20 nA without reaching critical radiation levels, resulting in a measurement time of 5–10 s per spot. This enabled acquiring in total 3070 NRA points on the central 46 × 46 mm 2 cut-outs of each sample and an adjacent part of equal size within 12 h of analysis time. The layers contained 50–60% D, 2% 12 C, and 3% O. The central 20 mm radius around the injection hole contains 98% of the total 13 C deposition. NRA finds up to 5.8 ± 0.9 × 10 22 13 C/m 2 close to the hole with an e-folding fall-off length of about 3–10 mm in every radial direction. In the D discharge 24 ± 2% and 16 ± 2% in He of the injected 13 C are found on the tiles with triangle shaped deposition profiles following ExB. The comparison to colour fringe analysis and SIMS reveals the particular strength of D-NRA regarding roughness, thick layers, and the separation of 12 C and 13 C deposits, but in compatible regions all methods agree. Compared to these, the NRA yields additional information indicating depositing species and physical processes.